Low-temperature heat-activated foamable sealing material
By using a combination of azodicarbonamide, water-insoluble urea or guanidine derivatives and zinc carboxylate salts, the problem of existing thermally activated foamable sealants being difficult to foam and crosslink at low temperatures has been solved, resulting in a high-efficiency, low-cost, and low-moisture-sensitivity sealing material suitable for low-temperature electrophoretic coating systems in automotive manufacturing.
Patent Information
- Application Number
- CN202480036165.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2024-05-31
- Publication Date
- 2026-01-13
AI Technical Summary
Existing thermally activated foamable sealants are difficult to effectively foam and crosslink at low temperatures, and pose health risks, are costly, and are highly sensitive to moisture, thus failing to meet the needs of low-temperature electrophoretic coating systems in automobile manufacturing.
By using a combination of azodicarbonamide, water-insoluble urea or guanidine derivatives and zinc carboxylate, the activation temperature is reduced to 140°C or lower. Thermally conductive fillers and antioxidants are used to avoid moisture absorption and health risks, ensuring that the sealing material can effectively foam and crosslink at low temperatures.
It achieves efficient foaming and cross-linking at low temperatures, has a high volume expansion rate, reduces health risks and costs, and reduces moisture sensitivity, making it suitable for low-temperature electrophoretic coating systems in automotive manufacturing.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims priority to U.S. Provisional Application No. 63 / 470,049, which is incorporated herein by reference in its entirety for all purposes. Technical Field
[0003] This invention relates to a low-temperature or cooling-activated foamable sealing material that maintains long-term latency when stored at room temperature. Background Technology
[0004] For passenger comfort, protection of electronic equipment, and corrosion prevention, the automotive industry involves sealing vehicle interiors to isolate them from noise, rain, snow, dust, moisture, fuel fumes, and other contaminants. Sealing strategies employed in the automotive industry include the use of heat-activated foamable sealants, which cross-link upon thermal activation. These sealants (whether supplied as pre-formed solids, pressure-sensitive tapes, flowable liquids, or pumpable pastes) utilize existing ovens in automotive assembly plants and are activated in one or more processing steps for curing various coatings applied to the vehicle, such as electrophoretic coatings, paints, etc.
[0005] Heat-activated sealing materials are typically applied early in the vehicle assembly process, in what is commonly known as the body-in-white. The body-in-white refers to the frame and sheet metal components fastened together by welding, riveting, bolting, or other methods. It provides access to tunnels, cavities, gaps, and other spaces requiring sealing.
[0006] After assembling the body-in-white, an electrophoretic coating (“e-coat”) is typically applied and cured in an oven. It is desirable to match the crosslinking and foaming activation temperatures of the thermally activated sealant material with the curing temperature of the electrophoretic coating system. Typically, existing electrophoretic coating systems require the substrate to be coated to reach a temperature of at least 160°C for at least 15 minutes, although it is possible to reach 200°C or higher for 40 minutes or longer.
[0007] Recent efforts in the field of electrophoretic coating curing have led to the development of electrophoretic coating systems that cure at temperatures as low as 140°C. Examples of such systems include ENVIRO-Prime® Epic, commercially available from PPG Industries, Inc., and CathoGuard®, commercially available from BASF. Curing at lower temperatures allows for significant energy savings relative to conventional electrophoretic coating systems. In addition, by allowing the body-in-white unit to pass through the oven more quickly, higher throughput of body-in-white units can be achieved relative to conventional electrophoretic coating systems. In this regard, the body-in-white often does not reach the actual temperature of the oven because of the mass of metal to be heated and because portions of the metal are shielded by other structures. Low temperature electrophoretic coating curing is beneficial in the manufacture of electric vehicles because the battery compartment is often constructed of a large amount of metal that can act as a heat sink and protect other areas of the vehicle from the oven heat, thus those other areas can not reach the oven temperature during a typical cycle time.
[0008] It is generally preferred to apply or insert the sealing material at the body-in-white assembly stage. However, sealing areas are often required at later stages of assembly, for example, at the paint spraying portion of the assembly operation. The operating temperature of a paint shop oven is generally lower than an electrophoretic coating oven, sometimes as low as 120°C.
[0009] Past efforts to achieve low activation temperatures in foamable sealing materials have utilized blowing agents with inherently lower activation temperatures, such as p,p’-oxybis(benzenesulfonyl hydrazide) (“OBSH”) or p-toluenesulfonyl hydrazide (“TSH”). However, these blowing agents are considered to have greater health risks, have higher cost, are generally available from fewer suppliers, and provide lower gas release per unit weight upon decomposition relative to blowing agents that activate at higher temperatures (e.g., azodicarbonamide, N,N’-dinitrosopentamethylenetetramine, and 5-phenyltetrazole (“5PT”)). With respect to gas release, OBSH, TSH, and the like face challenges in formulating sealing materials that can volumetrically expand by 1,000% or more, 1,500% or more, or even 2,000% or more. In addition, for applications requiring an activation temperature of 140°C or less, OBSH, TSH, and the like require further activation with additives such as urea or substituted ureas.
[0010] Endothermic blowing agents (e.g., sodium bicarbonate or potassium bicarbonate) can have an activation temperature of 150°C or less. However, these blowing agents also provide a lower gas release per unit weight. Thus, endothermic blowing agents face challenges in formulating a sealant that can volumetrically expand 1,000% or more, 1,500% or more, or even 2,000% or more due to the amount required to achieve these volume percentages. Endothermic blowing agents also face challenges in humidity sensitivity because they are typically salts with significant water solubility and are prone to absorbing moisture from the atmosphere. Moisture absorption interferes with the foaming process, the absorbed water itself acts as a blowing agent that is activated at relatively low temperatures, often producing large open cell structures and / or cell collapse.
[0011] Azodicarbonamide (“ADCA”) is a preferred thermally activated blowing agent in many applications, including the foaming of baked goods and the foaming of polymeric materials for cushioning and sealing. ADCA is generally considered to have a low health hazard rating, low cost, higher availability, and high gas release per unit weight relative to the blowing agents described above. One potential limitation of ADCA is its high activation or decomposition temperature. Unactivated ADCA is reported to have a decomposition temperature of up to 200-210°C. The activation temperature of ADCA can be reduced to a temperature that allows its use in a wide range of applications. A number of compounds are known ADCA decomposition activators, used alone or in combination with other activators. For example, the addition of a small amount (e.g., about 1-2 wt%) of zinc oxide is capable of activating ADCA at temperatures of 160°C or less. Urea and substituted ureas are also known ADCA decomposition activators, which can reduce the activation temperature of ADCA to 160°C or less in small amounts (e.g., about 1 wt% or less). Urea and most substituted ureas are effective activators, but are highly water soluble and thus sensitive to humid environments, triggering the problems described above resulting from water absorption.
[0012] There are limitations to reducing the activation temperature of ADCA by the methods described above. For example, when reducing the activation temperature of ADCA with zinc oxide, a zinc oxide content of about 1 wt% to 2 wt% has a significant effect in reducing the activation temperature, but a zinc oxide content above about 2 wt% has minimal effect on further reducing the activation temperature.
[0013] Small amounts of urea can reduce the activation temperature of ADCA to more practical working levels with minimal impact on other properties of the foamable sealant material. Urea amounts of up to 1%, 2%, or even more (by weight) have been used to reduce the activation temperature to 140°C or less (see, for example, U.S. 11,192,995 B2, which is incorporated by reference herein in its entirety for all purposes). However, due to the high water solubility of urea and even some substituted ureas, materials containing urea in amounts of 2% or more by weight are prone to water absorption prior to thermal activation, which can adversely affect the properties of the foamable sealant material (e.g., foaming prior to crosslinking results in reduced final volume expansion and poor cell structure). These adverse effects occur when the material is exposed to high relative humidity for even a short period of time (e.g., 4 days or less, 3 days or less, or even 2 days or less). In addition, urea imparts an amine-like odor to the material when cured.
[0014] Other methods have been used to reduce the activation temperature of ADCA, such as combinations of zinc complexes with amines, amides, and ureas, which have been reported to reduce the activation of ADCA to 160°C or even lower. For example, reaction products of zinc compounds and amines are provided by the introduction of JP 1980133433 A, which is incorporated herein in its entirety. Similarly, zinc dicyanatodiamine has been reported to be an effective activator of ADCA when used in combination with zinc oxide (see, Rubber World, August 1, 1993, which is incorporated herein in its entirety for all purposes). However, zinc dicyanatodiamine, as well as other zinc amine complexes, present significant health hazards and many are also prone to moisture sensitivity.
[0015] Some have employed combinations of heavy metal compounds, which include compounds or salts of zinc, used alone or in combination with other compounds, to reduce the activation temperature of ADCA to 160°C or even lower. A particularly common solution includes zinc compounds and nitrogen-containing compounds such as amines, amides, and ureas. U.S. Patent No. 3,305,496 A, which is incorporated herein in its entirety for all purposes, provides that heavy metal salts of monovalent alkali metals can reduce the activation temperature of finely divided ADCA to as low as 130°C to 140°C. However, to improve solubility in plastic compositions, a fatty acid amine or amide is included in the blowing agent composition as a dispersant. U.S. Patent No. 3,321,413 A, which is incorporated herein in its entirety for all purposes, similarly shows a composition including a heavy polyvalent metal salt, including a zinc salt, an alkali metal salt, and an aliphatic hydroxyl amine.
[0016] U.S. Patent Nos. 4,554,294 A and 4,634,721 A, incorporated by reference in their entirety for all purposes, provide that combinations of zinc salts of nitrosoureas or zinc oxides and nitrosoureas can be used to activate ADCA.
[0017] U.S. Patent No. 4,655,962 A, incorporated by reference in its entirety for all purposes, provides that ADCA can be activated at low temperatures with combinations of zinc oxides or zinc carbonates, zinc salts of Ci-C6organic acids, and zinc Ci-C6carboxamides.
[0018] Combinations of the heavy metal compounds, alkali metal salts, and amines or other nitrogen-containing compounds present some challenges. Some compounds are highly toxic, most particularly compounds of cadmium and lead. The addition of alkali metal salts can increase moisture uptake of the system to be foamed. In addition, the presence of alkali metal salts can be detrimental to the corrosion resistance of metals when the foamable material is in contact with un-painted metal surfaces (e.g., for sealing cavities or reinforcing metal sheets).
[0019] Many nitrogen-containing compounds tend to cause moisture uptake, particularly hydroxylated amines and ureas and their derivatives. The presence of some nitrogen-containing compounds limits the types of reactive groups that can be incorporated into the foamable system, as these functional groups tend to react with the nitrogen-containing compounds or are induced to react in the presence of the nitrogen-containing compounds. For example, primary amines will react with acrylic monomers, which are often added as co-agents for peroxide crosslinking of rubber or plastic foams, by Michael addition. Nitrogen-containing compounds such as amines, ureas, and imidazoles can induce the reaction of epoxy-functional compounds, which are often added to foamable polymer systems to increase strength or stiffness or to promote adhesion to metal substrates.
[0020] It can be desirable to provide a sealant material that is heat-activated to foam and / or crosslink.
[0021] It can be desirable to provide a sealant material that foams and / or crosslinks at a temperature of about 160°C or less, more preferably about 140°C or less, or even more preferably about 120°C or less.
[0022] It can be desirable to provide a sealant material that uses a blowing agent with an alterable activation temperature.
[0023] It can be desirable to provide a sealant material that foams and / or crosslinks within 20 minutes or less, 15 minutes or less, or even 10 minutes or less after a metal substrate on which the material is disposed reaches a target temperature (e.g., an oven temperature).
[0024] It can be desirable to provide a sealant material that foams and / or crosslinks in an electrocoat oven and / or in an oven in which the material is exposed after later stages of vehicle assembly (e.g., a paint bake oven).
[0025] It can be desirable to provide a sealant material that uses a blowing agent that has a relatively low health risk; has a relatively low cost; is readily available on the market; has a gas release that can provide a volume expansion of about 1,000% or more, about 1,500% or more, or even about 2,000% or more; is relatively less sensitive to moisture; or any combination thereof (relative to the conventional blowing agents described above).
[0026] It can be desirable to provide a sealant material that uses an activator that has low moisture sensitivity, has a relatively low health risk, does not negatively affect the corrosion resistance of the substrate metal, does not react with and / or facilitate the reaction of functional groups present on typical ingredients at normal processing temperatures of the foamable material, does not require a dispersant, or any combination thereof. SUMMARY
[0027] The present disclosure provides a foamable sealant material that can satisfy at least some of the above-described needs. The foamable sealant material can include one or more polymeric materials, an azodicarbonamide as a blowing agent, a water-insoluble urea or guanidine derivative, and optionally a zinc carboxylate salt. The water-insoluble urea or guanidine derivative and the zinc carboxylate salt cooperatively lower the activation temperature of the azodicarbonamide. Although the present invention contemplates that the water-insoluble urea or guanidine derivative can be present without the zinc carboxylate salt, it is preferred that the foamable sealant material can include the water-insoluble urea or guanidine derivative and the zinc carboxylate salt.
[0028] The activation temperature of the azodicarbonamide can be lowered to about 160°C or less, more preferably about 140°C or less, or even more preferably 120°C or less.
[0029] The water-insoluble urea or guanidine derivative can be dicyandiamide.
[0030] The zinc carboxylate salt can be a polymeric zinc ionomer.
[0031] The zinc carboxylate salt can be based on a carboxylic acid having 8 or more carbon atoms.
[0032] The zinc carboxylate salt can be selected from the group consisting of a zinc salt of one or more long chain carboxylic acids, zinc stearate, zinc laurate, zinc caprylate, zinc neodecanoate, zinc 2-ethylhexanoate, and zinc octoate, or any combination thereof.
[0033] The zinc carboxylate salt can be a zinc salt of one or more long chain carboxylic acids.
[0034] The long chain carboxylic acid can have a carbon chain length of C6 to C18.
[0035] The long chain carboxylic acid can include a mixture of saturated carboxylic acids and unsaturated carboxylic acids.
[0036] The one or more polymeric materials can include one or more elastomers, thermoplastic elastomers, thermoplastic polymers, polyolefin plastomers, polyolefin elastomers, or any combination thereof.
[0037] The one or more elastomers can include ethylene propylene rubber, ethylene propylene diene rubber, styrene butadiene rubber, nitrile butadiene rubber, polybutadiene rubber, natural rubber, isobutylene-isoprene rubber, or any combination thereof.
[0038] The one or more thermoplastic elastomers can include one or more block copolymers of styrene with butadiene or isoprene (e.g., styrene-butadiene-styrene, styrene-isoprene-styrene, styrene-ethylene-propylene-styrene, styrene-ethylene-butylene-styrene, or any combination thereof).
[0039] The one or more polymeric materials can include a copolymer and / or terpolymer of ethylene.
[0040] The one or more polymeric materials can include ethylene, polyethylene (e.g., low density polyethylene and / or linear low density polyethylene), ethylene octene, ethylene hexene, ethylene butene, n-butyl acrylate copolymer, ethylene vinyl acetate copolymer, ethylene n-butyl acrylate GMA terpolymer, or any combination thereof.
[0041] The foamable sealant can further include a thermally conductive filler.
[0042] The thermally conductive filler can include iron powder, aluminum powder, zinc powder, aluminum nitride, aluminum oxide (“alumina”), zinc oxide, graphite, graphene, iron phosphide, strontium ferrite, graphite boron nitride, silicon carbide, or any combination thereof.
[0043] The thermally conductive filler can be present in an amount of about 5% to 30% by weight of the foamable sealant.
[0044] The water-insoluble urea or guanidine derivative can be present in an amount of about 0.5% to about 5% by weight of the foamable sealant.
[0045] The zinc carboxylate salt can be present in an amount of about 0.5% to about 5% by weight of the foamable sealant.
[0046] The azodicarbonamide can be present in an amount of about 2% to about 15% by weight of the foamable sealant.
[0047] The azodicarbonamide can have a particle size distribution of about 1 micron to about 20 microns, as determined by ASTM UOP 856-07.
[0048] The foamable sealant material can be heat activated to foam and / or crosslink.
[0049] The volume of the foamable sealant material can increase by about 150% or more, 300% or more, 500% or more, 800% or more, 1,000% or more, 1,200% or more, or even 1,400% or more. The volume of the foamable sealant material can increase by about 2,200% or less, 2,000% or less, 1,800% or less, or even 1,600% or less.
[0050] The foamable sealant material can fully foam and / or crosslink in about 25 minutes or less, even more preferably about 20 minutes or less.
[0051] The volume of the foamable sealant material can increase by 1800% or more when heated to 140°C for 25 minutes.
[0052] The foamable sealant material can be free of dispersing agents.
[0053] The one or more polymeric materials can be present in an amount of about 40% to about 70% by weight of the foamable sealant material.
[0054] The foamable sealant material can further comprise an antioxidant. The antioxidant can be present with the thermally conductive filler.
[0055] The antioxidant can be derived from a sterically hindered phenol.
[0056] The antioxidant can be present in an amount of about 0.1% to about 2.5% by weight of the foamable sealant material.
[0057] The foamable sealant material can further comprise zinc oxide to lower the activation temperature of the azodicarbonamide.
[0058] The zinc oxide can be present in an amount of about 1% to about 15% by weight of the foamable sealant material.
[0059] The foamable sealant material can further comprise one or more crosslinking agents.
[0060] The crosslinking agent can include 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, dibenzoyl peroxide, benzoyl peroxide, methyl ethyl ketone peroxide, peroxydicarbonate, tert-butyl peroxide 2-ethylhexanoate, tert-butyl hydroperoxide, tert-butyl peracetate, tert-butyl perbenzoate, benzoyl peroxide, tert-amyl perbenzoate, tert-amyl peroxide 2-ethylhexanoate, peroxide 2,4-pentanedione, cumyl hydroperoxides, cumyl hydroperoxide, dicumyl peroxide, or any combination thereof.
[0061] The foamable sealant material can also include one or more crosslinking co-agents, one or more hydrocarbon resins, carbon black, oleamide, or any combination thereof.
[0062] The present disclosure provides a method of producing a foamable sealant material that can satisfy at least some of the aforementioned needs. The method can include premixing a zinc carboxylate salt with at least a portion of one or more polymeric materials. The method can include mixing the premix with a remaining portion, if any, of the one or more polymeric materials and an azodicarbonamide and a water-insoluble urea or guanidine derivative.
[0063] The method can include heating the foamable sealant material to about 160°C or less, more preferably about 140°C or less, or even more preferably 120°C or less.
[0064] The foamable sealant material can be heated for about 25 minutes or less, or even more preferably about 20 minutes or less.
[0065] The method can include increasing the volume of the foamable sealant material by about 150% or more, 300% or more, 500% or more, 800% or more, 1,000% or more, 1,200% or more, or even 1,400% or more; and increasing the volume of the foamable sealant material by about 2,200% or less, 2,000% or less, 1,800% or less, or even 1,600% or less. DETAILED DESCRIPTION
[0066] The present disclosure provides a foamable sealant material. The foamable sealant material can be heat-activated. The foamable sealant material can foam and / or crosslink at a low temperature relative to conventional foamable sealant materials. The foamable sealant material can be a thermoplastic or a thermoset.
[0067] The foamable sealant material can foam and / or crosslink at a temperature of about 160°C or less, 140°C or less, or even 120°C or less.
[0068] The foamable sealant material can have long-term latency. That is, the foamable sealant material can maintain a desired heat-activation response as a function of storage time.
[0069] The foamable sealant material can foam and / or crosslink in 20 minutes or less, 15 minutes or less, or even 10 minutes or less after the foamable sealant material and / or a substrate (e.g., a metal substrate) having the foamable sealant material disposed thereon reaches a target temperature (e.g., an oven temperature). For example, in a 25 minute bake cycle, it can take about 10 minutes for the substrate to reach the target temperature, and then the substrate and foamable sealant material can be exposed to an approximately constant temperature for 15 minutes.
[0070] The foamable sealant can expand in volume by about 150% or more, about 300% or more, about 500% or more, about 800% or more, about 1,000% or more, about 1,200% or more, or even about 1,400% or more. The foamable sealant can expand in volume by about 2,200% or less, about 2,000% or less, about 1,800% or less, or even about 1,600% or less.
[0071] The foamable sealant can achieve substantially no loss in volume expansion even when exposed to moisture (e.g., high humidity) prior to foaming and / or crosslinking. The foamable sealant exposed to moisture prior to foaming and / or crosslinking can have a loss in volume expansion of about 10% or less, 5% or less, or even 1% or less relative to the full expansion volume when not exposed to moisture. The foregoing can apply to exposing the foamable material to a temperature of about 35°C or less, a relative humidity of 85% or less, and storing for 3 days or less.
[0072] The foamable sealant can include one or more blowing agents ("blowing agent"). The blowing agent can be used to release a gas. The gas can cause the sealant to foam. The gas can be trapped in the polymer matrix of the foamable sealant, forming a cell structure. The gas can be more effectively trapped by crosslinking of the polymer matrix.
[0073] The blowing agent can include a chemical blowing agent. The chemical blowing agent can undergo a chemical reaction (decomposition) to release a gas (e.g., nitrogen, carbon monoxide, carbon dioxide, ammonia, or any combination thereof). The chemical reaction can be activated by heat (thermal decomposition). The chemical reaction can be exothermic (i.e., release heat during decomposition). Thus, the heat generated by the chemical reaction can supplement the heat provided by one or more external sources. The blowing agent can undergo thermal decomposition to release the gas.
[0074] The blowing agent can include azodicarbonamide ("ADCA"). The blowing agent can include at least ADCA and optionally one or more other blowing agents.
[0075] The particle size of the blowing agent can be used to adjust the rate of gas release at lower temperatures. Generally, the rate of gas release increases as the average particle size of the blowing agent decreases. The D90 of the particle size distribution of the blowing agent can be about 20 microns or less, more preferably about 15 microns or less, or even more preferably about 10 microns or less. The D90 of the particle size distribution of the blowing agent can be about 1 micron or more, 2 microns or more, 4 microns or more, or even 6 microns or more. The particle size distribution can be determined according to ASTM UOP 856-07, which is incorporated herein by reference for all purposes.
[0076] The blowing agent can be present in an amount of about 15% or less, about 13% or less, or even about 11% or less, by weight of the foamable sealant. The blowing agent can be present in an amount of about 2% or more, about 3% or more, about 5% or more, about 7% or more, or even about 9% or more, by weight of the foamable sealant.
[0077] The foamable sealant can include one or more blowing agent activators ("activators"). The blowing agent activators can be used to lower the activation temperature of one or more blowing agents relative to the activation temperature of the blowing agent in the absence of the blowing agent activator. The blowing agent activators can also change the relative ratio of the decomposition products of the gas produced.
[0078] The activation temperature can be lowered to about 160°C or less, about 140°C or less, or even about 120°C or less. The activation temperature can be lowered to about 90°C or more, about 100°C or more, or even about 110°C or more.
[0079] The blowing agent can decompose completely or almost completely (e.g., about 95% or more, about 97% or more, or even about 99% or more) in 20 minutes or less, 15 minutes or less, 10 minutes or less, or even 5 minutes or less at the foregoing temperatures in the presence of one or more activators.
[0080] The activators can include one or more nitrogen-containing compounds, one or more zinc-containing compounds (e.g., salts of long chain fatty acids), or both. The nitrogen-containing compounds can be solids. A solid, as referred to herein, can mean a solid at room temperature (i.e., about 20°C to 22°C).
[0081] The foamable sealant can include at least one or more nitrogen-containing compounds. To achieve an activation temperature lower than that achievable with the nitrogen-containing compound alone, a zinc-containing compound can be added to the foamable sealant. While most zinc complexes contribute to enhanced activation of the decomposition of blowing agents (e.g., ADCA), specific zinc complexes as described herein can be used to achieve particularly desirable properties.
[0082] The zinc-containing compounds and / or nitrogen-containing compounds can result in low water absorption of the foamable sealant. In particular, this can be achieved in polymer systems that include ethylene-containing polymers and copolymers (e.g., ethylene vinyl acetate and / or ethylene butyl acrylate, as well as other copolymers discussed above).
[0083] The zinc-containing compounds and / or nitrogen-containing compounds can allow for the incorporation of polymers and / or resins having reactive groups (e.g., acrylic or epoxy functional groups) into the foamable sealant. That is, the zinc-containing compounds and nitrogen-containing compounds can not react with the reactive groups of the polymers and / or resins.
[0084] The nitrogen-containing compound can include urea, guanidine, a modified urea compound, a modified guanidine compound, or any combination thereof. The modified urea and / or modified guanidine compound can be modified to obtain low water solubility.
[0085] The nitrogen-containing compound can include dicyandiamide. Dicyandiamide can have lower water solubility relative to other nitrogen-containing compounds (e.g., urea and some substituted ureas) that are commonly used as activators. It is well known that dicyandiamide is readily available from a variety of commercial sources and is less expensive relative to other nitrogen-containing compounds.
[0086] Dicyandiamide can react with and / or crosslink epoxy functional groups. Its activity with respect to epoxy addition reactions is thermally activated and can occur at temperatures within the typical, unaltered ACDA activation range (not the altered ACDA activation temperature range discussed herein). Thus, the activators of the present invention can be formulated with epoxy resins and epoxy-functional polymers (e.g., those containing glycidyl methacrylate as a co-monomer).
[0087] The nitrogen-containing compound can be present in an amount of about 0.5% or more, about 1.0% or more, about 1.5% or more, about 2.0% or more, or even about 2.5% or more, by weight of the foamable sealant material. The nitrogen-containing compound can be present in an amount of about 5% or less, about 4.5% or less, about 4.0% or less, about 3.5% or less, or even about 3.0% or less, by weight of the foamable sealant material.
[0088] Zinc oxide can activate ADCA and enhance activation of some nitrogen-containing compounds (e.g., urea or guanidine). However, due to low solubility and extremely high melting point, the activity of zinc oxide is dependent on particle size and additional reductions in activation temperature are negligible after a threshold of about 1% to 2% is reached. As described below, zinc oxide has the additional benefit of high thermal conductivity compared to many common mineral fillers (e.g., limestone, talc, or clay). Thus, zinc oxide can be used simultaneously as an activator and a thermally conductive filler.
[0089] The zinc-containing compound can include inorganic and / or organic zinc salts. Examples of inorganic zinc salts can include zinc phosphate. Organic zinc salts can include zinc salts of organic acids (e.g., benzenesulfonic acid or acetic acid).
[0090] The zinc-containing compounds can include one or more zinc carboxylate salts. The one or more zinc carboxylate salts can be used, preferably, alone or in combination with one or more other zinc-containing compounds. The zinc carboxylate salt can be water-insoluble, hydrophobic, or both. In this regard, low water absorption can be achieved; the expansion of the foamable sealant can be reduced negligibly (i.e., by 10% or less) or not at all; an excellent cell structure can be produced even after exposure to humidity of about 85% or less for a long period of time (i.e., about 1 day or more, about 2 days or more, or even about 3 days or more); or any combination thereof.
[0091] Lower molecular weight (i.e., C13 carbon chain or less) zinc carboxylate salts (e.g., zinc acetate) can be effective co-activators of insoluble urea or guanidine derivatives. However, lower molecular weight zinc carboxylate salts can have higher water absorption; lower volume expansion; and a poorer cell structure after exposure to humidity relative to higher molecular weight (i.e., C14 carbon chain or more) zinc carboxylate salts.
[0092] The zinc salt of a long-chain carboxylic acid can be characterized by one or more C6 or more, C8 or more, or even C10 or more carbon chains. The zinc salt of a long-chain carboxylic acid can be characterized by one or more C18 or less, C16 or less, or even C14 or less carbon chains. The zinc salt of a long-chain carboxylic acid can be saturated or unsaturated. The zinc salt of a long-chain carboxylic acid can include a single carbon chain length or more than one carbon chain length. The more than one carbon chain length can be characterized as being the same or different length. The long-chain carboxylic acid can be linear, branched, or a mixture thereof. The zinc salt of a long-chain carboxylic acid can be solid or liquid at room temperature (i.e., about 20°C to 22°C). The liquid zinc salt of a long-chain carboxylic acid can be advantageous to achieve complete distribution of the material throughout the polymer composition, thereby improving adhesion.
[0093] The zinc carboxylate salt can include a zinc salt of a long-chain carboxylic acid, zinc stearate, zinc laurate, zinc octoate, zinc neodecanoate, zinc 2-ethylhexanoate, zinc octoate, or any combination thereof. The zinc salt of a long-chain carboxylic acid can be preferred.
[0094] Zinc neodecanoate can be used because it is readily dispersible, hydrophobic, and has less impact on adhesion performance. Zinc neodecanoate, alone or in combination with one or more other zinc-containing compounds, can be preferred.
[0095] Zinc stearate and zinc laurate can reduce the adhesion of compositions containing them. Zinc stearate can be present in a slightly higher amount relative to other zinc carboxylate salts due to its lower zinc content.
[0096] Zinc stearate and zinc laurate can be pre-mixed with at least a portion of the polymeric material discussed herein at a temperature of about 110°C to 130°C (e.g., about 120°C) due to their relatively high melting temperatures. At this point, uniform dispersion and / or distribution can be ensured. After pre-mixing, the zinc stearate and polymeric material can be cooled prior to addition of the remaining polymeric and blowing agents. Cooling can avoid premature activation of the blowing agent.
[0097] The at least a portion or possibly all long chain carboxylic acids included in the composition can be characterized by unsaturation, branching, or both. Unsaturation and branching can impart a lower melting point, adhesion, adhesion durability, or any combination thereof. The zinc carboxylate salt can include a mixture of zinc salts of saturated fatty acids and unsaturated fatty acids.
[0098] Exemplary zinc salts of long chain carboxylic acids can include Dispergum L (zinc salts of C14-C18 saturated and unsaturated fatty acids) commercially available from DOG Deutsche Oelfabrik Ges. Fur chemische Erzeugnisse mbH and Co. KG.
[0099] The zinc carboxylate salt can be present in an amount of about 0.5% or more, about 1.0% or more, about 1.5% or more, about 2.0% or more, or even about 2.5% or more, by weight of the foamable sealant. The zinc carboxylate salt can be present in an amount of about 5% or less, about 4.5% or less, about 4.0% or less, about 3.5% or less, or even about 3.0% or less, by weight of the foamable sealant.
[0100] In the case where one or more zinc carboxylate salts and nitrogen-containing compounds are used together, they can be present in a weight ratio of zinc carboxylate salt to nitrogen-containing compound of about 0.2: 1 to 1:0.2, more preferably about 0.5: 1 to 1:0.5, or even more preferably about 0.8: 1 to 1:0.8 (e.g., about 1: 1). The ratio can be adjusted according to the weight content of zinc in each zinc carboxylate salt.
[0101] The activator and blowing agent can be present in a weight ratio of activator to blowing agent of about 1: 10 to 1: 1, more preferably about 1: 10 to 3: 10, more preferably about 1.5: 10 to 2.5: 10 (e.g., about 2.3: 10).
[0102] The foamable sealant can include one or more polymers. The polymer can be capable of softening, flowing, trapping gas released by the blowing agent, hardening, cross-linking, or any combination thereof.
[0103] Use of more than one polymeric material can be beneficial to obtain desired melting and / or softening properties of the polymeric matrix, to facilitate adhesion of the resulting foamable sealant (e.g., to the walls of a cavity, chamber, or channel to be sealed).
[0104] The one or more polymers can melt below the activation temperature of the blowing agent and / or blowing agent activator (e.g., about 160 °C or less, about 140 °C or less, or about 120 °C or less). In this regard, the polymeric component can be melted to mix with other ingredients while avoiding premature activation of the blowing agent and / or blowing agent activator.
[0105] The one or more polymers can be cross-linkable or vulcanizable to help trap gas, stabilize the resulting foam structure, facilitate adhesion to a surface, or any combination thereof.
[0106] The polymer can include an elastomer, a thermoplastic elastomer, a thermoplastic polymer, or any combination thereof.
[0107] The elastomer can be liquid at room temperature (i.e., about 20 °C to 22 °C). The liquid elastomer can change the viscosity of the material.
[0108] The elastomer can include an ethylene propylene rubber (“EPR”), an ethylene propylene diene rubber (“EPDM”), a styrene butadiene rubber (“SBR”), a nitrile butadiene rubber (“NBR”), a polybutadiene rubber, a natural rubber, an isobutylene-isoprene rubber (“IIR”), or any combination thereof.
[0109] The thermoplastic elastomer can include a block copolymer of styrene with butadiene or isoprene, such as styrene-butadiene-styrene (“SBS”) or styrene-isoprene-styrene (“SIS”). The block copolymer can be hydrogenated, such as styrene-ethylene-propylene-styrene (“SEPS”) or styrene-ethylene-butylene-styrene (“SEBS”).
[0110] The thermoplastic polymer can include an ethylene monomer. The thermoplastic polymer can include a polyethylene. The polyethylene can be low density or linear low density. The low density polyethylene can be an ethylene homopolymer with long chain branching. The linear low density polyethylene can be a linear copolymer of ethylene and a low molecular weight olefin (e.g., butene, hexene, or octene) to produce short chain branching.
[0111] The thermoplastic polymer can include one or more copolymers of ethylene with a polar comonomer. Suitable comonomers for polymerization with ethylene can include methyl acrylate, ethyl acrylate, butyl acrylate, glycidyl methacrylate, acrylic acid, methacrylic acid, vinyl acetate, or any combination thereof.
[0112] The thermoplastic polymer can include a terpolymer. The third monomer can be a functional monomer (i.e., having a reactive functional group). The functional monomer can be a monomer having additional reactive sites capable of participating in crosslinking the polymer composition and / or interacting with a surface to promote adhesion. The functional monomer can include glycidyl methacrylate (“GMA”), acrylic acid, methacrylic acid, maleic anhydride, or any combination thereof.
[0113] The additional reactive sites can be obtained by grafting the functional monomer onto the polyethylene and / or ethylene copolymer.
[0114] Exemplary polymers can include an ethylene n-butyl acrylate copolymer, an ethylene vinyl acetate copolymer, an ethylene n-butyl acrylate glycidyl methacrylate terpolymer, or any combination thereof.
[0115] The ethylene n-butyl acrylate copolymer can have a butyl acrylate content of about 15% to 40%. The ethylene vinyl acetate copolymer can have a vinyl acetate content of about 15% to 30%. The ethylene n-butyl acrylate glycidyl methacrylate terpolymer can have a butyl acrylate content of about 20% to 30% and a glycidyl methacrylate content of about 6% to 10%.
[0116] The ethylene n-butyl acrylate copolymer can have a melt flow index of about 1 g / 10 min to 1,000 g / 10 min. The ethylene vinyl acetate copolymer can have a melt flow index of about 1 g / 10 min to 1,000 g / 10 min. The ethylene n-butyl acrylate glycidyl methacrylate can have a melt flow index of about 1 g / 10 min to 1,000 g / 10 min. The melt flow index can be measured according to ASTM D1238.
[0117] The melt flow index of the one or more polymers can be selected depending on the desired expansion volume of the foamable sealant material. That is, a polymer having a lower flow can expand less than a polymer having a higher flow. This is taken into account with other components of the foamable sealant material, which can affect its rheological properties. A melt flow index that is too low can limit the formation and / or size of cells resulting from gas release. A melt flow index that is too high can reduce the gas trapping capacity of the polymer matrix.
[0118] The one or more polymers can be present in an amount of about 70% or less, about 65% or less, or even about 60% or less by weight of the foamable sealant material. The one or more polymers can be present in an amount of about 40% or more, about 45% or more, or even about 50% or more by weight of the foamable sealant material.
[0119] The foamable sealant material can include one or more crosslinking agents. Crosslinking agents can be used to create bonds between polymer molecules.
[0120] The polymer system can be crosslinked. Polymer materials that include unsaturation (i.e., carbon-carbon double bonds) can be crosslinked with elemental sulfur or a combination of sulfur and a cure promoter. Exemplary crosslinking agents can include dithiocarbamates, benzothiazoles (e.g., 2-mercapto-benzothiazole (“MBT”), 2-2’-dithiobis(benzothiazole) (“MBTS”)), thiourea, thiruams, and guanidine.
[0121] Carboxylated elastomers and thermoplastics can be crosslinked with hexamethylene diamine carbamate. Glycerol methacrylate-containing polymers can be crosslinked with latent amine curing agents (e.g., adipic acid dihydrazide (“ADH”) and dicyandiamide).
[0122] The crosslinking agent can include a latent organic peroxide. Latent organic peroxides are those that have a half-life of about 1 week to 6 months at room temperature (i.e., about 20°C to 22°C), but have a much shorter half-life (e.g., 1 hour or less) at the activation temperature of the blowing agent and blowing agent activator. Peroxides can be used to crosslink polymers with or without unsaturation in their structure.
[0123] Suitable organic peroxides can include dicumyl peroxide, di-(tert-butylperoxy isopropyl) benzene, 4,4-di(tert-butylperoxy) butyl valerate, benzoyl peroxide, methyl ethyl ketone peroxide, peroxydicarbonate, tert-butyl peroxide 2-ethylhexanoate, tert-butyl hydroperoxide, tert-butyl peracetate, tert-butyl perbenzoate, benzoyl peroxide, tert-amyl perbenzoate, tert-amyl peroxide 2-ethylhexanoate, peroxide 2,4-pentanedione, cumyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, or any combination thereof. Preferred peroxides can include 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, dibenzoyl peroxide, or any combination thereof.
[0124] To help trap the gas at temperatures of about 140°C or less, preferred organic peroxides are those that have a half-life of 6 minutes or less at a temperature of about 140°C. Preferred organic peroxides can include 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, dibenzoyl peroxide, or both.
[0125] The crosslinking agent can be present in an amount of about 3% or less, about 2.5% or less, or even about 2% or less, by weight of the foamable sealant material. The crosslinking agent can be present in an amount of about 0.5% or more, about 1% or more, about 1.5% or more, or even about 2% or more, by weight of the foamable sealant material.
[0126] The foamable sealant can include one or more crosslinking co-agents ("co-agents"). The co-agents can be used to enhance crosslinking, affect the peroxide decomposition temperature range, facilitate the trapping of gas generated by the blowing agent, or any combination thereof.
[0127] The co-agents can be di-, tri-, or multi-functional. The co-agents can include acrylate compounds, methacrylate compounds, vinyl compounds, allyl compounds, aliphatic maleimide compounds, aromatic maleimide compounds, or any combination thereof.
[0128] Suitable acrylate or methacrylate co-agents can include dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, or any combination thereof.
[0129] Suitable vinyl co-agents can include divinylbenzene, cyclohexanedimethanol divinyl ether, or both.
[0130] Suitable allyl co-agents can include triallyl cyanurate, triallyl isocyanurate, or both.
[0131] Suitable maleimide co-agents can include N,N'-m-phenylene bismaleimide, phenylmethane maleimide (CAS No. 67784-74-1), or both.
[0132] The co-agents can be present in an amount of about 3% or less, about 2% or less, about 1% or less, or even about 0.5% or less, by weight of the foamable sealant. The co-agents can be present in an amount of about 0.05% or more, about 0.1% or more, about 0.2% or more, or even about 0.3% or more, by weight of the foamable sealant. The amount of co-agent in the foamable sealant can be selected based on the functionality of the polymer, the desired rate of reaction, or both.
[0133] The foamable sealant can include one or more hydrocarbon resins. The hydrocarbon resins can be used to improve processability by reducing viscosity at high temperatures, facilitate adhesion to some types of substrates, or both.
[0134] The hydrocarbon resins can have a softening point of about 80°C or more, about 85°C or more, or even about 90°C or more. The hydrocarbon resins can have a softening point of about 110°C or less, about 105°C or less, or even about 100°C or less.
[0135] The hydrocarbon resins can include C5 resins, C9 resins, coumarone-derived hydrocarbons, rosin-based resins, or any combination thereof.
[0136] Hydrocarbon resins may be present in amounts of about 20% or less, about 18% or less, about 16% or less, or even about 14% or less by weight of the foamable sealant. Hydrocarbon resins may also be present in amounts of about 5% or more, about 8% or more, about 10% or more, or even about 12% or more by weight of the foamable sealant.
[0137] Foamable sealants may contain one or more thermally conductive fillers. These fillers can be used to increase the activation rate of the foaming agent (i.e., reduce the time required for complete decomposition). This can be achieved by increasing the rate of heat transfer to the foamable sealant.
[0138] Thermally conductive fillers and foaming agent activators can synergistically control the foaming of materials by lowering the inherent activation temperature of the foaming agent and reducing the time for complete volume expansion.
[0139] Thermally conductive fillers may include any thermally conductive particulate composition that is cost-effective for use in sealing materials. Particularly preferred options include iron powder, aluminum powder, zinc powder, aluminum nitride, aluminum oxide (“alumina”), zinc oxide, graphite, graphene, iron phosphide, strontium ferrite, graphite boron nitride, silicon carbide, or any combination thereof.
[0140] Thermally conductive fillers may be present in amounts of about 30% or less, about 25% or less, or even about 20% or less of the weight of the foamable sealant. Thermally conductive fillers may be present in amounts of about 2% or more, about 5% or more, about 10% or more, or even about 15% or more of the weight of the foamable sealant.
[0141] In some respects, thermally conductive fillers can be present in foamable materials at up to about 40% by weight or even about 50% by weight. The preferred weight percentage of the thermally conductive filler may depend on its properties, particularly its level of thermal conductivity, as well as its particle size, shape, and density. At this point, it is anticipated that these higher contents of thermally conductive fillers can be used in formulations with lower degrees of volume expansion (e.g., about 1000% or less, about 800% or less, or even about 500% or less). That is, as the polymer content decreases to accommodate the increased volumetric content of the thermally conductive filler, less polymer matrix may be available for forming cells through gas release.
[0142] Zinc oxide represents a unique case of a material that is both an activator of ADCA and has relatively high thermal conductivity. Therefore, at zinc oxide levels of, for example, about 15% by weight, the addition of zinc carboxylate compounds provides minimal benefit to volume expansion at, for example, about 140°C for about 25 minutes. Nevertheless, the addition of zinc carboxylate compounds can improve volume expansion at shorter baking times (e.g., about 15 minutes) and lower baking temperatures (e.g., about 135°C), and can also provide improvement in expansion after unactivated foamable sealants are exposed to high humidity. These benefits are illustrated in Tables 7A and 7B below.
[0143] The foamable sealing composition may contain one or more antioxidants. Antioxidants can be used to improve the temperature range of material foaming while reducing the tendency for degradation due to temperature exposure. Antioxidants have no adverse effect on volume expansion and cell structure (i.e., little effect on foaming activation temperature or decomposition rate).
[0144] Antioxidants allow the use of foamable sealing compositions at temperatures of about 170°C or higher (e.g., about 180°C or higher, about 190°C or higher, or even about 200°C or higher), thereby improving expansion at these temperatures. While the present invention discusses activation temperatures as low as 120°C or lower, foamable sealing compositions should generally exhibit consistent expansion at higher temperatures when exposed to them. For example, in high-volume manufacturing operations, oven temperatures may be higher than the required activation temperature to heat parts and compositions more quickly, although cycle times may be fast enough to prevent parts and / or compositions from heating themselves to oven temperatures. However, the composition should still provide consistent expansion at oven temperatures (e.g., about 180°C, about 190°C, or even about 200°C) in case of equipment failure or extended cycle times.
[0145] Unbound by theory, some thermally conductive fillers (e.g., iron and aluminum powders) can activate the peroxide-cured systems discussed above, leading to their decomposition at temperatures below their activation temperature. This decomposition can negatively impact the expansion properties of the composition. Antioxidants can mitigate or even prevent this decomposition.
[0146] Antioxidants can be advantageous when polymer systems are crosslinked with organic peroxides.
[0147] Antioxidants can be derived from hindered phenols. Hindered phenols may include butylated hydroxytoluene or pentaerythritol tetra(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).
[0148] Antioxidants may be present in amounts of about 2.5% or less, about 2% or less, or even about 1.5% or less by weight of the foamable sealant. Antioxidants may be present in amounts of about 0.1% or more, about 0.5% or more, or even about 1% or more by weight of the foamable sealant.
[0149] The expandable sealant composition may contain one or more anti-blocking agents or release agents. Exemplary anti-blocking agents or release agents may include oleamide. The anti-blocking agent or release agent may be present in an amount of about 0.1% or more, about 0.3% or more, or even about 0.5% or more by weight of the expandable sealant. The anti-blocking agent or release agent may be present in an amount of about 1.1% or less, about 0.9% or less, or even about 0.7% or less by weight of the expandable sealant.
[0150] Example
[0151] Table 1 provides a list of abbreviations and descriptions of the ingredients used throughout the embodiments. Ingredient names are provided in the embodiments where detailed descriptions are not required.
[0152]
[0153] Table 2A lists Examples I-1 to I-4 and Comparative Examples C-1 to C-2, which contain different combinations of dicyandiamide and aliphatic zinc carboxylate. The formulation was heated to induce foaming of the material under the following conditions: initially after mixing, after storage at 35°C and 85% relative humidity for 3 days, and after storage at 54°C for 3 days. Volume expansion was then performed at 140°C and 190°C for 25 minutes and 30 minutes, respectively. Table 2B summarizes the test results. The tests show that the composition containing both dicyandiamide and aliphatic zinc carboxylate exhibits improved volume expansion under exposure conditions of 140°C for 25 minutes. The benefit of this activator combination is obtained under prolonged exposure to high humidity (in this case, 3 days) prior to thermal activation.
[0154] The following tables reporting test results show the percentage increase in volume (expansion%) relative to the green state of the composition (i.e., before expansion) due to activation (e.g., at 140°C / 25 min) and the percentage of volume retained after storage under exposed conditions (e.g., at 35°C / 85% relative humidity for 3 days) (retention%). The moisture content provided below was determined according to ASTM D6304-20 (which is incorporated herein by reference for all purposes).
[0155] The densities reported in the following examples were measured according to ASTM D1505 (which is incorporated herein by reference for all purposes).
[0156]
[0157]
[0158]
[0159] The combination of dicyandiamide and zinc salts of long-chain carboxylic acids increases expansion compared to the absence of either component.
[0160] Table 3A lists Examples I-5 and I-6 of the present invention containing thermally conductive fillers. The non-thermally conductive calcium carbonate filler of Comparative Example C-3 was replaced with a thermally conductive filler at a volume substitution ratio of approximately 1:1. Example I-6 of the present invention also contains an antioxidant. The formulation was allowed to expand in volume after initial mixing, storage at 35°C and 85% relative humidity for 3 days, and after storage at 54°C for 3 days. Volume expansion was performed at 140°C and 190°C for 25 minutes and 30 minutes, respectively. Table 3B summarizes the test results. This test demonstrates some benefits of adding a thermally conductive filler to enhance expansion at low temperature (140°C) relative to Comparative Example C-3. In some cases, the addition of antioxidants can be beneficial to the overall foaming behavior, as demonstrated in Examples I-6, I-8, and I-9 of the present invention, where the expansion level at high activation temperatures (which is reduced in Example I-5 of the present invention) can be improved by adding antioxidants. Antioxidants are particularly beneficial for some thermally conductive fillers (such as iron and other metals) because these metals can activate the decomposition of organic peroxide curing agents.
[0161]
[0162]
[0163] Table 4A lists Examples I-7 to I-9 of the present invention containing antioxidants. These formulations were swelled in volume initially after mixing, after 3 days of storage at 35°C and 85% relative humidity, and after 3 days of storage at 54°C. Volume swelling was also performed at 140°C, 163°C, 177°C, and 190°C. Table 4B summarizes the test results. The tests also demonstrated some benefits of adding antioxidants to foaming properties, which were generally more significant at higher activation temperatures.
[0164]
[0165]
[0166] Table 5A lists Examples I-10 to I-13 of the present invention containing various thermally conductive fillers. The fillers were replaced so that each example contained nearly equal volumes of each component (including the thermally conductive filler). These formulations were subjected to volume expansion initially after mixing, after 3 days of storage at 35°C and 85% relative humidity, and after 3 days of storage at 54°C. Volume expansion was also conducted at 140°C, 163°C, 177°C, and 190°C. Table 5B summarizes the test results. Generally, strontium ferrite performed better than iron phosphide in terms of larger volume expansion, aluminum powder performed better than strontium ferrite, and boron nitride performed better than aluminum powder.
[0167]
[0168]
[0169] Table 6A lists Examples I-10 to I-14 of the present invention containing various carboxylates. These formulations were heated to cause expansion after initial mixing, after storage at 35°C and 85% relative humidity for 3 days, and after storage at 54°C for 3 days. Volume expansion was performed at 140°C, 163°C, 177°C, and 190°C. Table 6B summarizes the test results. The effectiveness of using C8, C10, and C18 saturated carboxylates is demonstrated.
[0170] In the embodiments of the present invention, various zinc carboxylate salts were added to provide nearly equal zinc content to these formulations. Comparative Examples C-3 and C-4 added zinc acetate at slightly lower and higher zinc levels than the embodiments of the present invention, respectively. While zinc acetate provides activation of the azodicarbonamide foaming agent, it was shown that this shorter-chain zinc carboxylate salt was more susceptible to the effects of high humidity exposure. Generally, the relatively longer chain length provides stronger moisture resistance; this benefit can exist independently of the influence of conductive fillers. After exposure at 35°C and 85% relative humidity for 3 days, swelling was significantly reduced. This was also observed in the moisture absorption level, which, for such exposure conditions, ranged from about 0.3% to above 0.4% depending on the level of zinc acetate added, while, according to the embodiments of the present invention, the moisture content was less than 0.15%, even below 0.1%, under the same conditions.
[0171] Examples I-14 were prepared by premixing a zinc compound with a portion of a polymer. It has been shown that premixing a zinc compound in a polymer before adding it to the formulation can be advantageous. This is especially true for zinc salts with higher melting temperatures, as their melting points are higher than the preferred mixing temperatures for heat-activated sealants. For example, zinc stearate melts at about 120°C, while the preferred maximum mixing temperature for heat-activated sealants is about 95°C, preferably 90°C, or even more preferably 85°C. Zinc stearate can be mixed with a polymer component at or above its melting point, without mixing with other reactive components, to form a masterbatch, which can then be incorporated into the final formulation at a lower temperature.
[0172] Aliphatic zinc carboxylate can be incorporated as a zinc ionomer in polymeric form. Zinc ionomers of ethylene, methacrylic acid copolymers, or ethylene-methacrylic acid-vinyl acetate terpolymers are commercially available from Dow Chemical Company under the trade name Surlyn™. Due to the high mixing temperature of zinc ionomers, it can be beneficial to blend the ionomers with lower melting point components (such as ethylene-vinyl acetate resins) to lower their melting point and allow incorporation of the ionomers at temperatures below the activation temperature of thermally activated foamable sealants.
[0173]
[0174]
[0175]
[0176] Table 7A lists Examples 1-15 to 1-16 of the present invention containing zinc oxide. Examples 1-15 do not contain zinc neodecanoate, while Examples 1-16 include zinc neodecanoate (liquid zinc salt). These formulations were heated to cause material expansion after initial mixing and after 3 days of storage at 35°C and 95% relative humidity. Heating was performed at approximately 135°C, 140°C, and 190°C. Table 7B summarizes the test results. The addition of zinc neodecanoate reduced the difference in foaming percentage between the highest and lowest temperatures used for foaming from 770 percentage points without zinc neodecanoate to 401 percentage points with zinc neodecanoate. Formulations containing zinc neodecanoate can be used in adhesives and tapes.
[0177]
[0178]
[0179] Table 8A lists Examples I-17 to I-19 of the present invention, which contain zinc neodecanoate and are suitable for adhesive and tape formulations. Initially after mixing, these formulations are heated to cause the material to expand. Volume expansion was performed at 140°C and 163°C. Table 8B summarizes the test results. The difference in low-temperature baking is evident in Comparative Example C-5, which lacks zinc neodecanoate and dicyandiamide.
[0180]
[0181]
[0182] Table 9A lists other examples of viscous expandable sealants I-20 and I-21 prepared according to the present invention. These examples contain dicyandiamide, zinc neodecanoate, high levels of zinc oxide as a thermally conductive filler, and a small amount of coated urea. It should be noted that the levels of zinc oxide in the examples of the present invention are much higher than those typically used in azodicarbonamide activation. Table 9B summarizes the results relative to Comparative Example C-6, a commercially available viscous sealant from L&L Products. It should be noted that the comparative material contains only 0.2% dicyandiamide, 2% zinc oxide, no coated urea, and no zinc neodecanoate. Example I-20 exhibits generally consistent expansion under both high and low temperature baking, which is desirable.
[0183]
[0184]
[0185] It should be understood that the above description is intended to be illustrative and not restrictive. Therefore, the specific embodiments of the invention described are not intended to be exhaustive or to limit the invention. Many embodiments and applications, in addition to the examples provided, will be apparent to those skilled in the art upon reading the above description.
[0186] Therefore, the scope of this invention should not be determined by reference to the above description, but rather by reference to the appended claims and the full scope of their equivalents. The omission of any aspect of the subject matter disclosed herein in the foregoing claims is not an abandonment of such subject matter, nor should it be construed as the inventor not considering such subject matter to be part of the disclosed inventive subject matter.
[0187] A single integrated element can provide multiple elements. Alternatively, a single element can be divided into multiple separate elements. The disclosure of "a" or "one" describing an element is not intended to exclude other elements.
[0188] While the terms first, second, third, etc., may be used herein to describe various components, these components should not be limited by these terms. These terms are used to distinguish one component from another. Terms such as “first,” “second,” and other numerical terms, when used herein, do not imply order or sequence unless the context clearly indicates otherwise. Therefore, the first component discussed herein may be referred to as the second component without departing from the invention.
[0189] The terms “approximately,” “substantially,” or “about” used to describe measurement results, percentages, or ratios can mean + / - 10% or less, + / - 5% or less, or even + / - 1% or less. The terms “approximately,” “substantially,” or “about” used to describe measurement results, percentages, or ratios can mean + / - 0.01% or more, + / - 0.1% or more, or even + / - 0.5% or more.
[0190] Unless otherwise stated, all ranges include both endpoints and all numbers in between. The terms “about” or “approximately” used with respect to a range apply to both ends of the range. Therefore, “about 20 to 30” is intended to encompass “about 20 to about 30”, including at least the specified endpoints.
[0191] Unless otherwise stated, any numerical value described herein includes all values from lower to higher values in increments of one unit, provided that there is an interval of at least two units between any lower and any higher value. As an example, if the stated value of a component quantity, performance, or process variable (e.g., temperature, pressure, time, etc.) is, for example, from 1 to 90, from 20 to 80, or from 30 to 70, it means that values in the intermediate range (e.g., 15 to 85, 15 to 85, 22 to 68, 43 to 51, etc.) are all within the scope of the invention described herein. Similarly, individual intermediate values are also within the scope of this teaching. For values less than 1, one unit is considered to be 0.0001, 0.001, 0.01, or 0.1, as appropriate. These are merely examples specifically pointed out, and all possible combinations of numerical values between the listed lowest and highest values are considered to be expressly stated in a similar manner in this application. Unless otherwise stated, all ranges include both endpoints and all numbers between the endpoints.
[0192] It can be seen that the teachings of amounts expressed in “parts by weight” in this document also take into account the same range expressed in terms of weight percentage. Therefore, the expression of a range expressed in terms of “at least 'x' parts by weight of the resulting composition” also takes into account the teachings of the same range of the amount “x” expressed as a weight percentage of the resulting composition.
[0193] The term "consistent essentially of..." used to describe a combination should include the identified elements, components, groups, or steps, as well as other elements, components, groups, or steps that do not materially affect the essential and novel features of the combination. The terms "comprising" or "including" used to describe a combination of elements, components, groups, or steps also consider embodiments that are substantially composed of elements, components, groups, or steps.
[0194] All publicly available content of articles and references (including patent applications and publications) is incorporated herein by reference for all purposes.
Claims
1. A foamable sealing material, comprising: One or more polymer materials, Azodicarbonamide, as a foaming agent, Water-insoluble urea or guanidine derivatives, and Optional zinc carboxylate salts; The water-insoluble urea or guanidine derivative and the zinc carboxylate salt synergistically reduce the activation temperature of the azodicarbonamide.
2. The foamable sealing material according to claim 1, wherein the activation temperature of the azodicarbonamide is reduced to about 160°C or lower, more preferably about 140°C or lower, or even more preferably 120°C or lower.
3. The foamable sealing material according to claim 1 or 2, wherein the water-insoluble urea or guanidine derivative is dicyandiamide.
4. The foamable sealing material according to any one of claims 1 to 3, comprising the zinc carboxylate salt.
5. The foamable sealing material according to any one of claims 1 to 4, wherein the zinc carboxylate is a polymerized zinc ionomer.
6. The foamable sealing material according to any one of claims 1 to 5, wherein the zinc carboxylate is based on a carboxylic acid having eight or more carbon atoms.
7. The foamable sealing material according to any one of claims 1 to 6, wherein the zinc carboxylate is selected from zinc salts of one or more long-chain carboxylic acids, zinc stearate, zinc laurate, zinc octanoate, zinc neodecanoate, zinc 2-ethylhexanoate, and zinc octanoate, or any combination thereof.
8. The foamable sealing material according to any one of claims 1 to 7, wherein the zinc carboxylate is a zinc salt of one or more long-chain carboxylic acids.
9. The foamable sealing material according to claim 7 or 8, wherein the long-chain carboxylic acid has a carbon chain length of C6 to C18.
10. The foamable sealing material according to any one of claims 7 to 9, wherein the long-chain carboxylic acid comprises a mixture of saturated and unsaturated carboxylic acids.
11. The foamable sealing material according to any one of claims 1 to 10, wherein the one or more polymeric materials comprise one or more elastomers, thermoplastic elastomers, thermoplastic polymers, or any combination thereof.
12. The foamable sealing material according to claim 11, wherein the one or more elastomers include ethylene propylene rubber, ethylene propylene diene monomer (EPDM), styrene-butadiene rubber (SBR), nitrile rubber, polybutadiene rubber, natural rubber, isobutylene-isoprene rubber, or any combination thereof.
13. The foamable sealing material according to claim 11 or 12, wherein the one or more thermoplastic elastomers comprise one or more block copolymers of styrene with butadiene or isoprene (e.g., styrene-butadiene-styrene, styrene-isoprene-styrene, styrene-ethylene-propylene-styrene, styrene-ethylene-butene-styrene, or any combination thereof).
14. The foamable sealing material according to any one of claims 11 to 13, wherein the one or more polymeric materials comprise copolymers and / or terpolymers of ethylene.
15. The foamable sealing material according to any one of claims 1 to 14, wherein the one or more polymeric materials comprise ethylene, polyethylene (e.g., low-density polyethylene and / or linear low-density polyethylene), ethylene octene, ethylene hexene, ethylene butene, n-butyl acrylate copolymer, ethylene vinyl acetate copolymer, ethylene n-butyl acrylate GMA terpolymer, or any combination thereof.
16. The foamable sealant according to any one of claims 1 to 15, wherein the foamable sealant further comprises a thermally conductive filler.
17. The foamable sealing material according to claim 16, wherein the thermally conductive filler comprises iron powder, aluminum powder, zinc powder, aluminum nitride, aluminum oxide, zinc oxide, graphite, graphene, iron phosphide, strontium ferrite, graphite boron nitride, silicon carbide, or any combination thereof.
18. The foamable sealant according to claim 16 or 17, wherein the thermally conductive filler is present in an amount of about 5% to 30% of the weight of the foamable sealant.
19. The foamable sealant according to any one of claims 1 to 18, wherein the water-insoluble urea or guanidine derivative is present in an amount of about 0.5% to about 5% by weight of the foamable sealant.
20. The foamable sealant according to any one of claims 1 to 19, wherein the zinc carboxylate is present in an amount of about 0.5% to about 5% by weight of the foamable sealant.
21. The foamable sealant according to any one of claims 1 to 20, wherein the azodicarbonamide is present in an amount of about 2% to about 15% by weight of the foamable sealant.
22. The foamable sealant according to any one of claims 1 to 21, wherein the particle size distribution of the azodicarbonamide is from about 1 micrometer to about 20 micrometers, as determined by ASTM UOP856-07.
23. The foamable sealant according to any one of claims 1 to 22, wherein the foamable sealant is thermally activated to foam and / or crosslink.
24. The expandable sealant according to any one of claims 1 to 23, wherein the volume of the expandable sealant is increased by about 150% or more, 300% or more, 500% or more, 800% or more, 1,000% or more, 1,200% or more, or even 1,400% or more; and wherein the volume of the expandable sealant is increased by about 2,200% or less, 2,000% or less, 1,800% or less, or even 1,600% or less.
25. The foamable sealant according to any one of claims 1 to 24, wherein the foamable sealant is fully foamed and / or crosslinked in about 25 minutes or less, or even more preferably about 20 minutes or less.
26. The foamable sealant according to any one of claims 1 to 25, wherein the foamable sealant increases in volume by 1800% or more when heated to 140°C for 25 minutes.
27. The foamable sealant according to any one of claims 1 to 26, wherein the foamable sealant is free of dispersant.
28. The foamable sealant according to any one of claims 1 to 27, wherein the one or more polymeric materials are present in an amount of about 40% to about 70% of the weight of the foamable sealant.
29. The foamable sealant according to any one of claims 1 to 28, wherein the foamable sealant further comprises an antioxidant.
30. The foamable sealing material of claim 29, wherein the antioxidant is derived from sterically hindered phenol.
31. The foamable sealant according to claim 29 or 30, wherein the antioxidant is present in an amount of about 0.1% to 2.5% by weight of the foamable sealant.
32. The foamable sealing material according to any one of claims 29 to 31, wherein the antioxidant is present together with the thermally conductive filler.
33. The foamable sealant according to any one of claims 1 to 32, wherein the foamable sealant further comprises zinc oxide to lower the activation temperature of the azodicarbonamide.
34. The foamable sealant of claim 33, wherein the zinc oxide is present in an amount of about 1% to 15% by weight of the foamable sealant.
35. The foamable sealant according to any one of claims 1 to 34, wherein the foamable sealant further comprises one or more crosslinking agents.
36. The foamable sealing material according to claim 35, wherein the crosslinking agent comprises 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, benzoyl peroxide, benzoyl peroxide, methyl ethyl ketone peroxide, dicarbonate peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl hydroperoxide, tert-butyl peracetate, tert-butyl perbenzoate, benzoyl peroxide, tert-amyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, 2,4-pentanedione peroxide, cumyl hydroperoxide, cumene hydroperoxide, dicumene peroxide, or any combination thereof.
37. The foamable sealant according to any one of claims 1 to 36, wherein the foamable sealant further comprises one or more crosslinking aids, one or more hydrocarbon resins, carbon black, oleamide, or any combination thereof.
38. A method for producing a foamable sealing material according to any one of the preceding claims, the method comprising: The zinc carboxylate salt is premixed with at least a portion of the one or more polymer materials; And to mix the premix with the remaining portion of the one or more polymer materials, if any, as well as the azodicarbonamide and the water-insoluble urea or guanidine derivative.
39. The method of claim 38, further comprising heating the foamable sealing material to about 160°C or lower, more preferably about 140°C or lower, or even more preferably 120°C or lower.
40. The method of claim 38 or 39, wherein the foamable sealant is heated for about 25 minutes or less, or even more preferably about 20 minutes or less.
41. The method according to any one of claims 38 to 40, further comprising increasing the volume of the foamable sealant by about 150% or more, 300% or more, 500% or more, 800% or more, 1,000% or more, 1,200% or more, or even 1,400% or more; and increasing the volume of the foamable sealant by about 2,200% or less, 2,000% or less, 1,800% or less, or even 1,600% or less.
Citation Information
Patent Citations
Foaming agent
JP1980133433A
Heat expandable foam for low temperature cure
US11192995B2
Activated azodicarbonamide
US3305496A
Activated azodicarbonamide blowing agent compositions
US3321413A
Nitro urea based blowing agents
US4554294A